Interactions between N‐Ethylmaleimide‐sensitive factor and GluA2 contribute to effects of glucocorticoid hormones on AMPA receptor function in the rodent hippocampus. Issue 7 (4th March 2016) - Xiong, Hui; Cassé, Frédéric; Zhou, Ming; Xiong, Zhi‐Qi; Joels, Marian; Martin, Stéphane; Krugers, Harm J.
ABSTRACT: Glucocorticoid hormones, via activation of their receptors, promote memory consolidation, but the exact underlying mechanisms remain elusive. We examined how corticosterone regulates AMPA receptor (AMPAR) availability in the synapse, which is important for synaptic plasticity and memory formation. Peptides which specifically block the interaction between N ‐Ethylmaleimide‐Sensitive Factor (NSF) and the AMPAR‐subunit GluA2 prevented the increase in synaptic transmission and surface expression of AMPARs known to occur after corticosterone application to hippocampal neurons. Combining a live imaging Fluorescence Recovery After Photobleaching (FRAP) approach with the use of the pH‐sensitive GFP‐AMPAR tagging revealed that this NSF/GluA2 interaction was also essential for the increase of the mobile fraction and reduction of the diffusion of AMPARs after treating hippocampal neurons with corticosterone. We conclude that the interaction between NSF and GluA2 contributes to the effects of corticosterone on AMPAR function. © 2016 Wiley Periodicals, Inc.